Civil Society, Political Mobilization, and the Impact of HIV Scale-up on Health Systems in Brazil - Parker, Richard G. (2009)
This article examines the role of civil society in shaping HIV and AIDS policies and programs in Brazil. It focuses on the historical context of the re-democratization of Brazilian society during the 1980s, when the initial response to the epidemic took shape, and emphasizes the role of social movements linked to the progressive Catholic Church, the sanitary reform movement in public health, and the emerging gay rights movement in the early response to the epidemic in Brazil. It highlights the broad-based civil society coalition that took shape over the course of the 1990s, and the political alliances that were built up shortly after the 1996 International AIDS Conference in Vancouver, Canada, in order to pass legislation guaranteeing the right to antiretroviral treatment access. It emphasizes the continued importance of civil society organizations – in particular, AIDS-related NGOS – and leading AIDS activists in exerting continued pressure in order to guarantee the sustainability of treatment access, and the impact that action focused on HIV and AIDS has had on the Brazilian public health system more broadly, particularly through strengthening health infrastructures and providing a model for health-related social mobilization more broadly.